Limits to tolerance: Tribal social order versus human rights - Kirchhoff Ferdinand Gerd; Khan Nazia (Temida)
In a globalized world, there are clear differences in ideologies that are usually not spelled out. The paper follows the approach prescribed by Ben David’s “Victim’s Victimology” (2000) and applies a classical approach to ideologies in social sciences by W.B. Miller (1973). The main subject of this paper is the difference between local order ideology and human rights ideology. The aim is to show that formal social control is determined or influenced by these different ideologies. The authors analyze four cases of victimization of women in different social settings , in Sudan (2012), Canada (2012), India (1985) and in Pakistan (2002). In all these cases the local order ideology clashes with a human rights ideology. Limits to tolerance must be clear.